Solid base supported metal catalysts for the oxidation and hydrogenation of sugars - Tathod, Anup; Kane, Tanushree; Sanil, E. S.; Dhepe, Paresh Laxmikant (Journal of Molecular Catalysis A-Chemical, 2014)
Pt impregnated on gamma-Al2O3 (acidic support) and hydrotalcite (basic support) catalysts were synthesized, characterized and used in the oxidation and hydrogenation reactions of C5 and C6 sugars. In the absence of homogeneous base, 83% yield for gluconic acid; an oxidation product of glucose can be achieved over Pt/hydrotalcite (HT) catalyst at 50 degrees C under atmospheric oxygen pressure. Similarly, 57% yield for xylonic acid, an oxidation product of xylose is also possible over Pt/HT catalyst. Hydrogenation of glucose conducted using Pt/gamma-Al2O3 + HT catalytic system showed 68% sugar alcohols (sorbitol + mannitol) formation. The 82% yield for C5 sugar alcohols (xylitol + arabitol) was obtained by subjecting xylose to hydrogenation over Pt/gamma-Al2O3 + HT at 60 degrees C. UV analysis helped to establish the fact that under alkaline conditions sugars prefer to remain in open chain form in the solution and thus exposes -CHO group which further undergoes oxidation and hydrogenation reactions to yield acids and alcohols. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Hydrogenation; Oxidation; Solid base; Sugars; Supported metal catalysts